HUBUNGAN ANTARA TINGKAT STRES DENGAN ANGKA KEJADIAN HIPERTENSI PADA USIA PRODUKTIF DI PUSKESMAS KEDATON BANDAR LAMPUNG - Upik Pebriyani; Nia Triswanti; Wega Fabia Prawira; Woro Pramesti (Medula, 2022)
Hypertension is a global public health problem and is the leading cause of premature death worldwide and has an increasing trend every year. Stress is a normal part of life that cannot be avoided. But too much stress can affect health. Increased stress levels will allow an increase in the prevalence of hypertension. To find out the relationship between stress levels and the incidence of hypertension at productive age at Kedaton Public Health Center Bandar Lampung. The research design used is descriptive analytic with cross sectional method. Sampling technique with total sampling method. Using spearmen's test analysis. Most of the respondents had moderate stress levels as many as 30 people (44.1%) and experiencing stage 1 hypertension as many as 34 people (50.0%). There is a significant relationship between stress levels and hypertension with p-value = 0.005. There is a significant relationship between stress levels and hypertension.